The World Book Dictionary (Vol.2) L-Z - World Book, Inc. (Rawalpindi, Pakistan Army Education Publishing House, 2001)
An English language dictionary which provides definitions, spellings, and pronunciations to more than 225,000 terms
Include Illustration
Keywords: English language